Increasing the stability of DNA nanostructure templates by atomic layer deposition of Al2O3 and its application in imprinting lithography - Kim, Hyojeong; Arbutina, Kristin; Xu, Anqin; Liu, Haitao (Beilstein Journal of Nanotechnology, 2017)
We present a method to increase the stability of DNA nanostructure templates through conformal coating with a nanometer-thin protective inorganic oxide layer created using atomic layer deposition (ALD). DNA nanotubes and origami triangles were coated with ca. 2 nm to ca. 20 nm of Al2O3. Nanoscale features of the DNA nanostructures were preserved after the ALD coating and the patterns are resistive to UV/O3 oxidation. The ALD-coated DNA templates were used for a direct pattern transfer to poly(L-lactic acid) films.
Keywords: aluminium oxide (Al2O3); atomic layer deposition; DNA nanostructure; nanofabrication; nanoimprint lithography; pattern transfer; polymer stamp; replica molding

(untitled) - Seeman, N. C. (J. Theor. Biol., 1982)

(untitled) - Seeman, N. C. (Annu. Rev. Biochem., 2010)

(untitled) - Zhang, F.; Nangreave, J.; Liu, Y.; Yan, H. (J. Am. Chem. Soc., 2014)

(untitled) - Liu, H.; Chen, Y.; He, Y.; Ribbe, A. E.; Mao, C. (Angew. Chem., Int. Ed., 2006)

(untitled) - Rothemund, P. W. K.; Ekani-Nkodo, A.; Papadakis, N.; Kumar, A.; Fygenson, D. K.; Winfree, E. (J. Am. Chem. Soc., 2004)

(untitled) - Tian, C.; Zhang, C.; Li, X.; Hao, C.; Ye, S.; Mao, C. (Langmuir, 2014)

(untitled) - Yin, P.; Hariadi, R. F.; Sahu, S.; Choi, H. M. T.; Park, S. H.; LaBean, T. H.; Reif, J. H. (Science, 2008)

(untitled) - Rothemund, P. W. K. (Nature, 2006)

(untitled) - He, Y.; Chen, Y.; Liu, H.; Ribbe, A. E.; Mao, C. (J. Am. Chem. Soc., 2005)

(untitled) - Wei, B.; Dai, M.; Yin, P. (Nature, 2012)

(untitled) - Zhang, F.; Jiang, S.; Wu, S.; Li, Y.; Mao, C.; Liu, Y.; Yan, H. (Nat. Nanotechnol., 2015)

(untitled) - Andersen, E. S.; Dong, M.; Nielsen, M. M.; Jahn, K.; Subramani, R.; Mamdouh, W.; Golas, M. M.; Sander, B.; Stark, H.; Oliveira, C. L. P.; Pedersen, J. S.; Birkedal, V.; et al. (Nature, 2009)

(untitled) - Chandrasekaran, A. R.; Levchenko, O. (Chem. Mater., 2016)

(untitled) - Han, D.; Pal, S.; Nangreave, J.; Deng, Z.; Liu, Y.; Yan, H. (Science, 2011)

(untitled) - Ke, Y.; Ong, L. L.; Shih, W. M.; Yin, P. (Science, 2012)

(untitled) - Becerril, H. A.; Ludtke, P.; Willardson, B. M.; Woolley, A. T. (Langmuir, 2006)

(untitled) - Shimada, J.; Maruyama, T.; Kitaoka, M.; Yoshinaga, H.; Nakano, K.; Kamiya, N.; Goto, M. (Chem. Commun., 2012)

(untitled) - Yan, H.; Park, S. H.; Finkelstein, G.; Reif, J. H.; LaBean, T. H. (Science, 2003)

(untitled) - Rahman, M.; Neff, D.; Norton, M. L. (Chem. Commun., 2014)

(untitled) - Chen, Y.; Liu, H.; Ye, T.; Kim, J.; Mao, C. (J. Am. Chem. Soc., 2007)

(untitled) - Keren, K.; Berman, R. S.; Buchstab, E.; Sivan, U.; Braun, E. (Science, 2003)

(untitled) - Li, S.; He, P.; Dong, J.; Guo, Z.; Dai, L. (J. Am. Chem. Soc., 2005)

(untitled) - Mangalum, A.; Rahman, M.; Norton, M. L. (J. Am. Chem. Soc., 2013)

(untitled) - Braun, E.; Eichen, Y.; Sivan, U.; Ben-Yoseph, G. (Nature, 1998)

(untitled) - Liu, J.; Geng, Y.; Pound, E.; Gyawali, S.; Ashton, J. R.; Hickey, J.; Woolley, A. T.; Harb, J. N. (ACS Nano, 2011)

(untitled) - Uprety, B.; Gates, E. P.; Geng, Y.; Woolley, A. T.; Harb, J. N. (Langmuir, 2014)

(untitled) - Pilo-Pais, M.; Goldberg, S.; Samano, E.; LaBean, T. H.; Finkelstein, G. (Nano Lett., 2011)

(untitled) - Pearson, A. C.; Liu, J.; Pound, E.; Uprety, B.; Woolley, A. T.; Davis, R. C.; Harb, J. N. (J. Phys. Chem. B, 2012)

(untitled) - Uprety, B.; Westover, T.; Stoddard, M.; Brinkerhoff, K.; Jensen, J.; Davis, R. C.; Woolley, A. T.; Harb, J. N. (Langmuir, 2017)

(untitled) - Jin, Z.; Sun, W.; Ke, Y.; Shih, C.-J.; Paulus, G. L. C.; Hua Wang, Q.; Mu, B.; Yin, P.; Strano, M. S. (Nat. Commun., 2013)

(untitled) - Deng, Z.; Mao, C. (Angew. Chem., Int. Ed., 2004)

(untitled) - Becerril, H. A.; Woolley, A. T. (Small, 2007)

(untitled) - Surwade, S. P.; Zhao, S.; Liu, H. (J. Am. Chem. Soc., 2011)

(untitled) - Surwade, S. P.; Zhou, F.; Wei, B.; Sun, W.; Powell, A.; O’Donnell, C.; Yin, P.; Liu, H. (J. Am. Chem. Soc., 2013)

(untitled) - Diagne, C. T.; Brun, C.; Gasparutto, D.; Baillin, X.; Tiron, R. (ACS Nano, 2016)

(untitled) - Zhou, F.; Sun, W.; Ricardo, K. B.; Wang, D.; Shen, J.; Yin, P.; Liu, H. (ACS Nano, 2016)

(untitled) - Helmi, S.; Ziegler, C.; Kauert, D. J.; Seidel, R. (Nano Lett., 2014)

(untitled) - Sun, W.; Boulais, E.; Hakobyan, Y.; Wang, W. L.; Guan, A.; Bathe, M.; Yin, P. (Science, 2014)

Polymer Science: A Comprehensive Reference - Lipomi, D. J.; Martinez, R. V.; Cademartiri, L.; Whitesides, G. M. (Soft Lithographic Approaches to Nanofabrication, 2012)

(untitled) - Totzeck, M.; Ulrich, W.; Göhnermeier, A.; Kaiser, W. (Nat. Photonics, 2007)

(untitled) - Manfrinato, V. R.; Zhang, L.; Su, D.; Duan, H.; Hobbs, R. G.; Stach, E. A.; Berggren, K. K. (Nano Lett., 2013)

(untitled) - Lin, B. J. (Proc. SPIE, 2012)

(untitled) - Wieland, M. J.; de Boer, G.; ten Berge, G. F.; van Kervinck, M.; Jager, R.; Peijster, J. J. M.; Slot, E.; Steenbrink, S. W. H. K.; Teepen, T. F.; Kampherbeek, B. J. (Proc. SPIE, 2010)

(untitled) - Pease, R. F.; Chou, S. Y. (Proc. IEEE, 2008)

(untitled) - Qu, J.; Hou, X.; Fan, W.; Xi, G.; Diao, H.; Liu, X. (Sci. Rep., 2015)

(untitled) - Tian, C.; Kim, H.; Sun, W.; Kim, Y.; Yin, P.; Liu, H. (ACS Nano, 2017)

(untitled) - Bonnet, J.; Colotte, M.; Coudy, D.; Couallier, V.; Portier, J.; Morin, B.; Tuffet, S. (Nucleic Acids Res., 2010)

(untitled) - Colotte, M.; Coudy, D.; Tuffet, S.; Bonnet, J. (Biopreserv. Biobanking, 2011)

(untitled) - Elam, J. W.; Sechrist, Z. A.; George, S. M. (Thin Solid Films, 2002)

(untitled) - Kim, H.; Surwade, S. P.; Powell, A.; O’Donnell, C.; Liu, H. (Chem. Mater., 2014)

(untitled) - Pillers, M. A.; Lieberman, M. (J. Vac. Sci. Technol., B, 2014)